2016
DOI: 10.5546/aap.2016.eng.313
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance and length of mechanical ventilation in children admitted to a single Pediatric Intensive Care Unit

Abstract: Introduction.Associations between cumulative fluid balance and a prolonged duration of assisted mechanical ventilation have been described in adults. The aim of this study was to evaluate whether fluid balance in the first 48 hours of assisted mechanical ventilation initiation was associated with a prolonged duration of this process among children in the Pediatric Intensive Care Unit (PICU). Methods. Retrospective cohort of patients in the PICU of Hospital Italiano de Buenos Aires, between 1/1/2010 and 6/30/20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…Sinitsky et al [ 11 ] found that diagnostic category was an independent prognostic factor in a study of the correlation between FO at 48 h and respiratory morbidity. Vidal et al [ 14 ] reported that respiratory and septic shock were related to prolonged MV in a study of the correlation between fluid balance and length of MV in children. In this study, the main reason for admission was even statistically significantly related to mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinitsky et al [ 11 ] found that diagnostic category was an independent prognostic factor in a study of the correlation between FO at 48 h and respiratory morbidity. Vidal et al [ 14 ] reported that respiratory and septic shock were related to prolonged MV in a study of the correlation between fluid balance and length of MV in children. In this study, the main reason for admission was even statistically significantly related to mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Extubation failure was defined as the reinstitution of MV within 48 h of extubation. Duration of MV longer than 7 days was concerned based on the effect of prolonged MV on prognosis [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Анализ констриктивной и либеральной стратегий инфузионной терапии показал, что первый вариант улучшал функцию легких, сокращал продолжительность механической вентиляции легких и интенсивной терапии без увеличения количества нелегочных осложнений, сокращал частоту проявления острой почечной травмы у пациентов с острым повреждением легких и острым респираторным дистресс-синдромом [15][16][17]. Метаанализ Silversides J.…”
Section: инфузионная терапия и респираторная системаunclassified
“…15 Positive fluid balance has shown to have a trend towards prolonged mechanical ventilation. 16 It has been found that a negative fluid balance of < 500 ml achieved in any of the first 3 days of septic shock is a good independent predictor of survival in patients with septic shock. 17 The higher cumulative fluid balance at third day after ICU admission was independently associated with an increase mortality hazard in sepsis patients, but not the higher fluid balance in the first 24 hours.…”
Section: Fluid Balancementioning
confidence: 99%